2007
DOI: 10.1002/cne.21305
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of α‐neurexins does not cause a major impairment of axonal pathfinding or synapse formation

Abstract: Alpha-neurexins are synaptic cell-surface molecules that are required for Ca(2+)-triggered exocytosis. Mice lacking all three alpha-neurexins show drastically reduced neurotransmitter release at excitatory and inhibitory synapses and die early postnatally. Although previous histological analysis of newborn alpha-neurexin triple mutants revealed only a moderate reduction in the density of type II synapses in the brainstem, cell culture studies proposed that neurexins are prominently involved in synapse formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
81
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 66 publications
7
81
1
Order By: Relevance
“…In addition to the calcium channel coupling phenotype, ␣-neurexin 1/2/3 triple knock-out mice had a 2-fold reduction in the density of type II symmetric GABAergic synapses in neonatal brainstem with no change in density of type I asymmetric glutamatergic synapses (27). A 30% reduction in type II symmetric synapses but not type I asymmetric synapses was also found in adult neocortex of neurexin 1/2␣ and 2/3␣ double knock-out mice (53). It was not clear whether this loss of inhibitory synapses reflected a direct function of ␣-neurexin in GABA synapse development or an indirect effect of reduced synaptic activity due to the presynaptic calcium channel coupling defect.…”
Section: Discussionmentioning
confidence: 93%
“…In addition to the calcium channel coupling phenotype, ␣-neurexin 1/2/3 triple knock-out mice had a 2-fold reduction in the density of type II symmetric GABAergic synapses in neonatal brainstem with no change in density of type I asymmetric glutamatergic synapses (27). A 30% reduction in type II symmetric synapses but not type I asymmetric synapses was also found in adult neocortex of neurexin 1/2␣ and 2/3␣ double knock-out mice (53). It was not clear whether this loss of inhibitory synapses reflected a direct function of ␣-neurexin in GABA synapse development or an indirect effect of reduced synaptic activity due to the presynaptic calcium channel coupling defect.…”
Section: Discussionmentioning
confidence: 93%
“…In support of this overall concept, ␣-neurexin triple KO mice exhibit major impairments in synaptic transmission that manifest largely, but not exclusively, as presynaptic changes (9)(10)(11)(12)(13). Importantly, ␣-neurexin KO mice do not display a major decrease in the number of excitatory synapses, and only a moderate decrease in inhibitory synapses (9,13). Thus, neurexins appear to be essential components of synaptic function whose roles extend to several different components of synapses.…”
mentioning
confidence: 77%
“…Studies with double and triple ␣-NRXN KO mice have indicated that ␣-NRXNs in neurons are essential for the organization and stabilization of the presynaptic machinery (21)(22)(23). In vitro work suggests that NRXNs interact with the synaptic vesicle-associated protein rabphilin-3A via CASK (24) and contribute to synaptic vesicle docking (16,25).…”
mentioning
confidence: 99%